Negosiasi Kekuasaan dalam Komunitas Adat: Komunikasi Politik dan Pemilihan Kepemimpinan di Negeri Hitumessing - Slamat, Siti Asma; Afdhal, Afdhal (Universitas Pattimura, 2024)
This study explores the dynamics of political communication in the appointment and election system of traditional leadership (Raja) in the indigenous community of Negeri Hitumessing, Maluku, as a form of power negotiation within adat structures. The research is grounded in the significance of understanding political communication processes within a sociocultural space that retains strong traditional values while being influenced by modernity. Employing a qualitative descriptive approach, data were collected through interviews, observations, and documentation involving community leaders, adat authorities, religious figures, youth representatives, and village officials. Political communication theory and Harold Lasswell’s model serve as the conceptual framework to analyze message transmission, actors involved, communication channels, and the resulting socio-political impacts. Findings reveal that the Raja election functions not only as a contest for authority but also as a symbolic arena for competing group interests. Communication channels are hybrid in nature—oral interactions through informal community networks coexist with digital expressions via social media, particularly Facebook, which facilitates public critique and opinion formation. The election process significantly affects social values, religious practices, and public perceptions of legitimacy. This study contributes a novel mapping of political communication’s role within adat institutions, offering insights for integrating political communication approaches in local leadership studies and strengthening community-based democracy in Indonesia.